The Bureau of Public Schools Music Series, grades I-VI, and the Ward Music Series, volumes I-VI, a comparative study - Yamzon, Alice C. 1931- (s.n.], 1972)
The primary concern of this thesis is to present a comparative study between the Bureau of Public Schools Music Series, Grades I-VI and the Ward Music Series, Volumes I-VI in order to determine what in the latter Series can improve the former Series.